A combined numerical-experiment investigation on the failure of a pressure relief valve in coal liquefaction. (February 2016) - Zheng, Zhijian; Ou, Guofu; Yi, Yuwei; Shu, Geping; Jin, Haozhe; Wang, Chao; Ye, Haojie
Abstract: In a direct coal liquefaction unit, pressure relief valves locate on the pipeline between the atmospheric and vacuum towers. Failures of the valve components occur frequently owing to the harsh operation conditions. A combined numerical-experiment investigation on the failures of valves is conducted in this paper. The variation of relative erosion rates of WC–Co coating with impact angles, the function of relative particle velocity, and the distribution of particle diameters are obtained from the high-temperature erosion experiments. Furthermore, the erosion mechanism of WC–Co coating under large impact angles is clarified. In the numerical simulation, the evaporation–condensation, particle motion, erosion, and the modified RNG k-ε turbulence models are used to analyze the phase transition and particle erosion in the valves. Results showed that: due to the high pressure drop and convergent–divergent structure of angle valve, the coal-oil slurry flashes as it enters into the valves. The evaporation of liquid oil produces a large amount of vapor oil, and results in a rapid increase in flow velocity. High concentration solid particles, driven by the high-speed stream, tend to erode the inner surface of valves. Severe erosion can be found in the spool of angle valve, downstream bushings at the angle valve and ball valve. The calculation results agree well with actual failure morphologies, verifies the accuracy of the present prediction method. Highlights: A numerical-experimental investigation on valve's failure is conducted. Erosion rates of WC–Co under high-temperature environment are obtained. Essential functions of erosion model are calculated based on experiments. Failure is caused by particles erosion during evaporation of liquid oil. Numerical results agree well with failure morphologies of valve components.